Attitudes Of Generation Y Towards Luxury Products And Youth-Led Change In Luxury Consumption Behaviour - Yazıcı, Belgin (The Turkish Online Journal of Design Art and Communication, 2016)
To many people luxury products were once considered hard to access and a privilege to use. Luxury used to mean a product or service only accessible by a small group of people, a product or service that was scarce (Nueno & Quelceh, 1998). However, luxury products have now become more affordable to more consumers, especially for consumers from the middle class who access more money than ever before (Hauck & Stanforth, 2007) and therefore luxury brands have the chance to flourish and establish their reputation worldwide. In order to do so, they must truly understand their consumers – and recognise how they are changing. Besides the drivers of their decisions, the purchasing behaviors of consumers are evolving. Consumers prefer to be engaged with digital channels in terms of their buying processes. Generation Y has a tremendous impact of the world economy because of the number of its representatives and increasing purchasing power, so it has been transforming into the biggest consumer segment throughout history. As a result of this, Generation Y attracts the attention of many scientific fields from psychology to economics. The main question is what makes this generation so unique both as a research topic for scientific studies and a marketing challenge. Young adults who were born between 1980 and 1990 are considered to be Generation Y and this generation has ended up to become the largest part of global consumer market and it has become an undeniable fact for luxury brands that their motivations and attitudes have to taken into consideration in the process of developing products. The brands need to communicate with the representatives of Generation Y effectively. The aim of this article is to examine Generation Ys’ attitudes, i.e. their beliefs, feelings and purchase intentions towards luxury products and the meanings of the word “luxury” to young people, reasons for buying luxury products, and, on a small scale, young adults’ luxury brand awareness and brand loyalty. In addition, this study aims at not only examining Generation Y customers’ luxury purchasing behaviour but also helping organizations understand such customers’ needs and wants. It is widely acknowledged that understanding consumer behavior is the key to be successful in business and this youth- led change in luxury consumption behavior should not be underestimated to be able to attract the attention of the future powerhouse of the global economy.
Keywords: Generation Y; millenials; luxury consumption; luxury brands; new luxury; luxury marketing; Generation Henry; Y jenerasyonu; Milenyum kuşağı; lüks tüketim; lüks markalar; yeni lüks; lüks market; Henry jenerasyonu